Industry Change Through Vertical Disintegration: How and Why Markets Emerged in Mortgage Banking - Jacobides, Michael G. (Academy of Management Journal, 2005)
By providing a theoretical framework that explains how and why vertical dis-integration happens, this inductive longitudinal analysis of the mortgage banking value chain sheds light on one of the least studied aspects of industry evolution. I find that gains from specialization set off a process of intra-organizational partitioning, which leads to coordination simplification along parts of the value chain; and gains from trade foster inter-firm co-specialization, which leads to information standardization. As a result of standardized information and simplified coordination, new intermediate markets emerge, even in the presence of transactional risks. This breaks up the value chain, allowing new types of industry participants to emerge, thus, changing the competitive landscape.